Pt-based nanoarchitecture and catalyst design for fuel cell applications - Jung, Namgee; Chung, Dong Young; Ryu, Jaeyune; Yoo, Sung Jong; Sung, Yung-Eun (ELSEVIER SCI LTD, 2014)
Recent advances in multistructured nanocatalysts and support materials for polymer electrolyte membrane fuel cells (PEMFCs) are reviewed. Discussions focus on the materials' structures and compositions, which significantly affect the electronic structures and catalytic activities of fuel cell catalysts. The nanocatalyst category includes metal alloys (including shape-controlled alloy nanoparticles), and core shell and hollow structures. Various carbons (carbon blacks, carbon nanotubes, carbon nanofibers, and graphenes) and metal oxides are extensively explored as support materials. We describe the physical and electrochemical meanings of the nanoarchitectured catalysts and support materials mainly for the oxygen reduction reaction (ORR), because high ORR activity is one of the most important factors in enhancing PEMFC efficiency. Based on progress in catalysis and fuel cell technologies in recent decades, we suggest promising future research topics for PEMFC commercialization. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: OXYGEN REDUCTION REACTION; WALLED CARBON NANOTUBES; CORE-SHELL NANOPARTICLES; ELECTROCATALYTIC ACTIVITY; ALLOY NANOPARTICLES; ELECTROCHEMICAL CHARACTERIZATION; NONCOVALENT FUNCTIONALIZATION; MONOLAYER ELECTROCATALYSTS; PTXNI1-X NANOPARTICLES; HOLLOW NANOPARTICLES